The Idea of «Concept» in the Studies of Culture - T. D. Tatarskaya (MGIMO University Press, 2014)
The article is devoted to analyzing the difference between discourses about "concept". It is an attempt to reveal the features of these approaches to the problem of understanding and studying of "concept". This term is currently at its peak popularity in the human studies, which is connected with its universality and the process of globalization, which generates an interest to studying cultures though these keywords or concepts. Meanwhile, the discourse about "concept" firstly appeared in philosophical literature. Then at the early twentieth century an interest to "concept" arose in Russian linguistics. Afterwards, the term came from the field of pure linguistics to the fields of cognitive linguistics and cultural linguistics, and then in the first decade of XXI century it was rekindled thanks to philosophy. Nowadays in the modern humaninities there are the coexistence of different approaches to understanding, interpretation and investigation of concept. In terms of linguistics the concept constitutes the meaning of sign, and its investigation focused on the search of different means of representation of it in the language and on the basis on them structuring the concept. Linguocognitive science has its aim in building a cognitive model of representation this term in the linguistic consciousness of a native speaker. The feature of cultural linguistics approach is its orientation on the search of cultural component of concept. And the approach of cultural studies focused on the search of the features and the analysis of the essence of this phenomenon in the general context of culture